Application of sappan wood natural colour with the addition of limau citrus for making candied dried fruit - Sari, Dina Yuspita (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2025)
Desa Karimunting has the potential for medicinal plants, such as nutmeg, sappan wood, lime citrus, and fruits. Sappan wood contains the antioxidant brazilin, which can give an orange to red color, depending on the pH. Meanwhile, lime citrus contains citric acid, which is used to modify the color produced by sappan wood. This PkM aims to provide education and training in making candied dried fruit with modified natural dyes from sapan wood and limau citrus. The method used provided material followed by training in making candied dried fruit. The PkM results were examined through a pre and post-test, and then the data was processed using the t-test. Evaluation of the program was performed using a Likert scale. The results acquired are candied dried fruit products with various colors. Based on the evaluation results, there was a growth in participants' understanding from 67 to 82.43, implied by a substantial difference between the pre and post-test results. The index value of opinion is 98.67% in the very satisfied category. This shows that PkM activities can supply education and skills for the community in processing fruit plantation products into candied dried fruit, which is beneficial for health and has economic potential.